Inadequate Cerebrospinal Fluid Concentrations of Available Salvage Agents Further Impedes the Optimal Treatment of Multidrug-Resistant Enterococcus faecium Meningitis and Bacteremia - Eric Wenzler; Alina Adeel; Tiffany Wu; Michele Jurkovic; Jeremy Walder; Emily Ramasra; Maureen Campion; Jan Cerny; Nicole M. Theodoropoulos (MDPI AG, 2021)
Background: Vancomycin-resistant Enterococcus faecium (VRE) in particular has evolved as an important cause of hospital acquired infection, especially in immunocompromised hosts. Methods: We present a complex case of a patient with relapsed acute myeloid leukemia who underwent allogenic hematopoietic stem cell transplantation complicated by persistent VRE bacteremia and meningitis. To optimize therapy, various blood and cerebrospinal fluid (CSF) samples were sent to a research laboratory for extensive susceptibility testing, pharmacokinetic analyses, and time-kill experiments. Results: In vitro testing revealed resistance to all first-line treatment options and CSF sampling demonstrated sub-optimal central nervous system concentrations achieved by each antimicrobial agent administered in relation to their respective MIC value. Time-kill analyses at observed CSF concentrations confirmed the lack of bactericidal activity despite use of a four-drug combination regimen. Conclusions: This work is the first to report CSF concentrations of oritavancin and tedizolid in humans and adds to the limited data regarding in vitro susceptibility of new antimicrobial agents such as eravacycline, omadacycline, and lefamulin against VRE. Our study provides new insights into various aspects of treatment of extensively drug-resistant Enterococcus faecium meningitis and bacteremia and supports the continued pursuit of precision medicine for these challenging cases.